LEVEL UP PERFORMANCE: THE ROLE OF COMPETENCE AND TRAINING THROUGH MOTIVATION AT KPPN PAMEKASAN WORK UNIT - Maulana, Wahyu; Nopriyanto, Indra (Universitas Multimedia Nusantara, 2025)
Abstract - HR is a key factor in the success of an organization, including the government sector. In the context of accelerating budget absorption, the role of the SATKER treasurer is very crucial. This study aims to analyze the effect of competence, motivation, and training on employee performance in supporting the acceleration of budget absorption in the Pamekasan KPPN work area. The type of quantitative research with a descriptive approach. The population in this study were all SATKER treasurers totaling 105 people with a saturated sampling technique. Data collection was carried out through a Likert-scale questionnaire. Data analysis used SEM PLS through the SmartPLS application with outer and inner model assessment indicators. The results of the study showed that competence and motivation didn't have a positive and insignificant effect on performance while training had a positive and significant effect on performance. Indirectly, competence didn't have a significant but significant effect on motivation while training didn't have a significant effect on motivation. The results of the mediation test showed that motivation didn't mediate the relationship between competence and training on performance. These findings indicate the importance of increasing training for SATKER treasurers to support the effectiveness of budget absorption and state financial reform.. Keywords: Performance; Competence; Training; Motivation; KPPN Pamekasan